POTRET SOSIAL EKONOMI PETUGAS PARKIR WANITA LANSIA DI KABUPATEN ACEH BARAT - Wilda Muhfira; Afrizal Tjoetra; Triyanto Triyanto; Ligar Abdillah (Jurnal Society : Pengamat Perubahan Sosial, 2022)
The purpose of this study was to analyze and find out the various driving factors behind elderly women choosing jobs as parking attendants in West Aceh District. In addition, this study also aims to describe the socio-economic conditions of elderly women who work as parking attendants. Elderly women are a physically vulnerable group and can be targeted by criminals, such as fraud, violence, harassment, and discrimination. The theory used in this research is Coleman's rational choice. This study uses a descriptive qualitative method that prioritizes in-depth interviews with informants to obtain information relevant to the research focus. Qualitative research methods are also very useful for describing research results. The results of this study indicate that elderly women choose jobs as parking attendants mostly due to less established economic conditions. They hope that working as a parking attendant can solve their economic problems and can improve their social welfare.